PENINGKATAN MUTU AIR SUMUR SIAP MINUM MELALUI FILTRASI DENGAN BIAYA EKONOMIS - suharjo; Abdul Hamid; Kiantoro; Arby Pratama Putra Rosmin (Jurnal Pendekar Nusantara, 2024)
Water is one of important substance for human being. Good water for daily needs has to be clean, no colour and odorless. Other than that for consumtion good water also has to contain important minerals needed by human body. The villagers of Kampung Melayu RW 01 Kelurahan Setokok , Kecamatan Bulang uses rain water and digging well to get water for their daily needs. This water does not meet basic requirements for daily needs. In community service activity programme in 2020, the students of Mechanical Engineering of Engineering Faculty Uniba conducted education for the villagers on the importance of clean water for life and how to get it at low cost. The education focused on technical matter to get clean water by filtration system. Filtration method uses plastic bottle, gravel, cotton, charcoal and water tubing to purify water. After purification by filtration system water meets all requirements as stated in Indonesian Goverment Law Number 20 year 1990 on water quality standard. Keyword: filtration, purification, standard water.